Hantavirus and Leptospira are important causes of nonspecific acute febrile syndrome, Meta, Colombia - Liliana Sánchez-Lerma; Salim Mattar; Verónica Contreras; Jorge Miranda; Vaneza Tique; Virginia Rodríguez; Derly Rodriguez; Sonia Lopez; Andrés Rojas-Gulloso (Travel Medicine and Infectious Disease)
Introduction: Acute undifferentiated febrile illnesses are fevers lasting less than fourteen days without an evident focus of infection on the initial physical examination or with inconclusive laboratory tests. Objective: Carry out epidemiological surveillance of the etiology of acute undifferentiated febrile syndrome in the Meta department. Methods: A descriptive, prospective cross-sectional study was carried out between February 2021 and June 2023 in a first-level hospital in the department of Meta, Colombia. All enrolled patients underwent routine hematology and blood biochemistry examinations. RT-qPCR was performed for Dengue and serology for laboratory diagnoses using ELISA and MAT for Hantavirus and Leptospirosis, respectively. A descriptive and bivariate analysis was performed using SPSS vr 23.0. Results: Of the study's total of one hundred patients, 14 % showed antibodies against hantavirus IgG, of which two were seroconverted. In addition, a risk factor OR = 8.3 (CI = 1.8–38.4) for Hantavirus was found in those patients who had contact with farm animals. Regarding leptospirosis, 3 % of the sera agglutinated with titers greater than 1:400, resulting in a primary infection; 11 % of the sera presented agglutination with titers no greater than 1:200 as exposure to leptospirosis. The bivariate analysis showed an OR = 2.4; CI = 0.75–7.4 with water recreational activities in the last 30 days before the onset of symptoms. Conclusions: Our study demonstrates the importance of Hantavirus, Dengue, and leptospirosis as a cause of acute undifferentiated febrile illnesses. Coinfections are frequent in one of the tropical areas of Colombia, so it is crucial to establish a more precise diagnosis.